(untitled) (Journal of Armed Forces Medical College, Bangladesh, 2015)
Introduction: It is easier to evaluate the patients satisfaction towards the service than to evaluate the quality of medical services that they receive. Therefore, a probe into patient satisfaction can provide an important tool to improve the quality of services. Patient satisfaction is a multi-dimensional healthcare issue affected by many factors. Healthcare quality affects patient satisfaction and results in positive influences on patient behaviour such as confidence in hospital care. Objectives: The objective of the study was to evaluate the problems of recipients and service providers during service delivery at out patient departments of a tertiary level hospital. Materials and Methods: This cross sectional descriptive study was conducted on the patients attending the medical out patient departments along with the service providers, administrative personnel and supportive staffs of a government hospital during the period of February 2007 to June 2007. Results: A total of 299 patients, 5 service providers, 8 administrative personnel and 11 supporting staffs were purposively selected in the study. Among 299 respondents,169 (56%) identified patient overload as the most common problem. As many as, 70(24%) patients experienced more than 4 hours delay in the hospital. Less than half 117(39%) of the patients experienced the problem of not getting proper consultancy due to absence 26 JAFMC Bangladesh. Vol 9, No 2 (December) 2013 of physician in their chambers. Although 117(39%) patients faced multiple problems during undergoing investigation in the hospital, 21% patients were satisfied partially with hospital staff support. Out of 5 service providers 3(60%) worked in a congested space. As many as 20% service providers reported that patients were not satisfied by the service of MOPD. Monthly pay and allowances were not sufficient (as observed by 80% of respondents). The study also revealed that lack of co-operation amongst the staffs and inadequate pay and salary were the main problems in 75% of the administrative personnel. Moreover, 55% supportive staff faced patient overload. All the service providers opined that improvement of medical outpatient service requires adequate manpower. Conclusion: Most of the service providers, administrative personnel and supportive staffs are facing hardship with the present pay and allowances leading to extra work after office hour. Most common suggestions of the patients, service providers, administrative personnel and supportive staffs were to employ more health personnel. They also suggested strengthening of supervisory system to ensure strict discipline at all levels. DOI: http://dx.doi.org/10.3329/jafmc.v9i2.21822 Journal of Armed Forces Medical College Bangladesh Vol.9(2) 2013